2019
DOI: 10.1002/1873-3468.13357
|View full text |Cite
|
Sign up to set email alerts
|

A readout of metabolic efficiency in arylamine N‐acetyltransferase‐deficient mice reveals minor energy metabolism changes

Abstract: Recent studies have revealed a possible link between the activities of polymorphic arylamine N‐acetyltransferases (NATs) and energy metabolism. We used a Nat1/Nat2 double knockout (KO) mouse model to demonstrate that ablation of the two Nat genes is associated with modest, intermittent alterations in respiratory exchange rate. Pyruvate tolerance tests show that double KO mice have attenuated hepatic gluconeogenesis when maintained on a high‐fat/high‐sucrose diet. Absence of the two Nat genes also leads to an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
1
1
Order By: Relevance
“…A pyruvate tolerance test suggests the null animals had compromised hepatic gluconeogenesis. There was also a modest increase in hepatic CoA without a change in acetyl-CoA (Denis et al, 2019). Interestingly, this study did not identify major metabolic changes that were reported for the mNat1 null mice.…”
Section: Studies With Mnat Null Mouse Modelscontrasting
confidence: 59%
See 1 more Smart Citation
“…A pyruvate tolerance test suggests the null animals had compromised hepatic gluconeogenesis. There was also a modest increase in hepatic CoA without a change in acetyl-CoA (Denis et al, 2019). Interestingly, this study did not identify major metabolic changes that were reported for the mNat1 null mice.…”
Section: Studies With Mnat Null Mouse Modelscontrasting
confidence: 59%
“…NAT1 and NAT2 both affect mitochondrial fuel usage and mitochondrial respiration, although the generality of these observations across different cells and tissues is currently not known (Chennamsetty et al, 2016;Denis et al, 2019;Wang et al, 2019). The paucity in work on co-expression of NAT1 and NAT2 emphasises the need to better understand how these proteins are regulated, whether their expressions are coordinated, and whether they show any functional redundancy.…”
Section: Nat Coordination and Reciprocitymentioning
confidence: 99%